2020
DOI: 10.1093/jisesa/ieaa132
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Aldehyde Oxidase 5 in the Pheromone Gland of the Silkworm (Lepidoptera: Bombycidae)

Abstract: Aldehyde oxidases (AOXs) are a subfamily of cytosolic molybdo-flavoenzymes that play critical roles in the detoxification and degradation of chemicals. Active AOXs, such as AOX1 and AOX2, have been identified and functionally analyzed in insect antennae but are rarely reported in other tissues. This is the first study to isolate and characterize the cDNA that encodes aldehyde oxidase 5 (BmAOX5) in the pheromone gland (PG) of the silkworm, Bombyx mori. The size of BmAOX5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…For instance, our analyses revealed 5 full-length and 1 partial AOX sequences for P. xylostella, including the only identified AOX so far (PxylAOX3) (Wang et al, 2021b). Similarly, 9 full-length sequences were identified for B. mori, including BmorAOX1, BmorAOX2, and BmorAOX5, the only AOXs reported so far (Pelletier et al, 2007;Zhang et al, 2020). Likewise, we report 2 new AOXs for H. armigera, in which 6 AOXs had previously been reported, including HarmAOX2, suggested to be a candidate pheromone-degrading enzyme (Xu and Liao, 2017).…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…For instance, our analyses revealed 5 full-length and 1 partial AOX sequences for P. xylostella, including the only identified AOX so far (PxylAOX3) (Wang et al, 2021b). Similarly, 9 full-length sequences were identified for B. mori, including BmorAOX1, BmorAOX2, and BmorAOX5, the only AOXs reported so far (Pelletier et al, 2007;Zhang et al, 2020). Likewise, we report 2 new AOXs for H. armigera, in which 6 AOXs had previously been reported, including HarmAOX2, suggested to be a candidate pheromone-degrading enzyme (Xu and Liao, 2017).…”
Section: Discussionmentioning
confidence: 56%
“…For instance, odorant-binding proteins (OBPs) and chemosensory proteins (CSPs) function as transporters that carry odorants across the sensillar lymph (Zhou, 2010;Leal, 2013). These odorants reach an heteromeric complex of receptors, such as odorant receptors (ORs), an odorant receptor co-receptor (Orco) and a sensory neuron membrane protein (SNMP), as recently reported (Zhang et al, 2020), to unleash depolarization in olfactory neuron membranes that triggers a behavioral response (Kaissling, 2013). Along with these olfactory proteins, odorant-degrading enzymes (ODEs), such as carboxylesterases (CXEs), glutathione-S-transferases (GSTs) and aldehyde oxidases (AOXs), are responsible for resetting the insect olfactory system through the degradation of odorant molecules (Chertemps and Meïbèche, 2021;Godoy et al, 2021).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…HarmAOX2 is a candidate ODE to inactivate the sex pheromone components (Z)-11-hexadecenal and (Z)-9-hexadecenal (Xu and Liao, 2017). Recombinant AtraAOX2, PxylAOX3, BmAOX5 from the A. transitella , P. xylostella and B. mori , respectively, could degrade the sex pheromone or plant-derived volatiles in vitro (Choo et al ., 2013; Zhang et al ., 2020; Wang et al ., 2021). Therefore, we further need to prove this conjecture by expressing AOX protein in vitro to verify whether it can bind sex pheromone substances.…”
Section: Discussionmentioning
confidence: 99%
“…Functional research on AOXs showed that the recombinant AtraAOX2, which was the first activity characterization of a recombinant insect AOX in vitro , could degrade sex pheromone and plant volatile aldehydes as substrates (Choo et al ., 2013), which indicated that AOX did play a role in inactivating odorant molecules. Meanwhile, BmAOX5 in the pheromone gland of B. mori participates in the degradation of aldehyde pheromone substances and odorant compounds also illustrates this point (Zhang et al ., 2020). Recently, the activity analysis of AOX acting on substrates in vitro revealed that PxylAOX3 from the antennae of Plutella xylostella protected olfactory neuron by inactivation of redundant odorants and detoxification of xenobiotics (Wang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%